2003
DOI: 10.1016/s0306-4573(02)00044-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithms in relevance feedback: a second test and new contributions

Abstract: The present work is the continuation of an earlier study which reviewed the literature on relevance feedback genetic techniques that follow the vector space model (the model that is most commonly used in this type of application), and implemented them so that they could be compared with each other as well as with one of the best traditional methods of relevance feedback--the Ide dec-hi method. We here carry out the comparisons on more test collections (Cranfield, CISI, Medline, and NPL), using the residual col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Others who have used this measure include Fan et al (2006) and Horng & Yeh (2000). Lopez-Pujalte et al (2002) and Lopez-Pujalte et al (2003b) provide an extensive survey on 12 fitness functions, and found that the choice of fitness function was essential when guiding GA's through the search space. Other examples include use of the Guttman model, a statistical measure of rank correlation which has many of the same properties of average precision according to Tamine et al (2003).…”
Section: Fitness Functionsmentioning
confidence: 99%
“…Others who have used this measure include Fan et al (2006) and Horng & Yeh (2000). Lopez-Pujalte et al (2002) and Lopez-Pujalte et al (2003b) provide an extensive survey on 12 fitness functions, and found that the choice of fitness function was essential when guiding GA's through the search space. Other examples include use of the Guttman model, a statistical measure of rank correlation which has many of the same properties of average precision according to Tamine et al (2003).…”
Section: Fitness Functionsmentioning
confidence: 99%
“…In regard to search methods, most research studies have employed evolutionary algorithms (EAs). The EA flexibility enables the modeling of rank learning in many ways, such as through ranking function discovery [5,13,14], weight and parameter learning [15][16][17][18][19], among others. Independent to the model representation, a proper evaluation function is very important for the effectiveness and efficiency of EAs.…”
Section: Introductionmentioning
confidence: 99%
“…Although REFs have been shown to have applied a major rule to rank learning almost a decade ago [13,[15][16][17], in recent studies, little attention has been given to the design http://www.journal-bcs.com/content/20/1/7 and selection of more appropriate ones. Researchers have chosen popular REFs and applied them to new contexts and models without any theoretical or empirical evidence about its suitableness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Getting the exact answer is a fundamental requirement for the traditional applications of DBMS, based mainly on numbers and small character strings. However, new DBMS are being increasingly required to support more complex data types such as images, videos, audio, time series and DNA sequences, among others [1]. This type of data management systems approach has given rise to Multimedia Digital Databases (MDD).…”
Section: Introductionmentioning
confidence: 99%